Rancang Bangun Alat Monitoring Kelembaban, PH Tanah dan Pompa Otomatis Berbasis Arduino - Ronald Daniel (Journal of Applied Computer Science and Technology, 2022)
In today's era technology has begun to enter into various aspects of human life, one of which is in the field of agriculture. The majority of farmers in Indonesia still carry out farming activities without using technology assistance. This of course has its own advantages and disadvantages, and one of the drawbacks is not knowing the cause of why a plant dies but not because of disease or not growing plants optimally and watering plants in large quantities at certain times every day. Based on the problems above, the author tries to design a tool that can monitor the state of the soil and also carry out watering automatically, using the prototyping method. Tools and materials used such as arduino nano as a microcontroller, humidity sensor to read the value of moisture in the soil and soil pH sensor to read the pH value of the soil. The tool will send data to the user's smartphone so that it can be monitored and controlled by the pump remotely. It is hoped that the tool can ease the workload of farmers or can also provide additional information regarding the condition of the soil where the plants grow